Ewolucja procesu karnego w Polsce na tle zasad kontradyktoryjności i inkwizycyjności – zarys problematyki - Łaskawski, Grzegorz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Celem niniejszego artykułu jest przedstawienie zarysu problematyki ewolucji modelu procesu karnego na tle zasad kontradyktoryjności i inkwizycyjności, ze szczególnym uwzględnieniem ich genezy, rozwoju w średniowiecznej Europie oraz Polsce, a także późniejszej modyfikacji polskiego modelu procesu karnego aż do czasów współczesnych.

The aim of this article is to present an outline of the issues of the evolution of the model of criminal procedure against the background of the principles of adversarial and inquisitorial principles, with particular emphasis on their genesis, development in medieval Europe and Poland, as well as later modification of the Polish model of criminal procedure, up to the present day.
Evolution of the criminal procedure in Poland in the background of the principles of adversarial and inquisitorial – an outline of the problem
Keywords: proces karny; zasady procesowe; kontradyktoryjność; inkwizycyjność; criminal procedure; procedural rules; adversarial process; inquisitory process